2020
DOI: 10.1073/pnas.1916960117
|View full text |Cite|
|
Sign up to set email alerts
|

The intelligent knife (iKnife) and its intraoperative diagnostic advantage for the treatment of cervical disease

Abstract: Clearance of surgical margins in cervical cancer prevents the need for adjuvant chemoradiation and allows fertility preservation. In this study, we determined the capacity of the rapid evaporative ionization mass spectrometry (REIMS), also known as intelligent knife (iKnife), to discriminate between healthy, preinvasive, and invasive cervical tissue. Cervical tissue samples were collected from women with healthy, human papilloma virus (HPV) ± cervical intraepithelial neoplasia (CIN), or cervical cancer. A hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 49 publications
(60 reference statements)
2
56
0
9
Order By: Relevance
“…A number of mass spectrometry studies have previously reported satisfactory diagnostic accuracy of cervical cancer or pre-cancer, however these were performed either on cervical tissue samples 27 , rendering it unsuitable as a screening approach, or using more laborious and time-consuming approaches 9 , [11] , [12] , [13] . Different studies employing vibrational spectroscopic approaches, including Raman and infrared spectroscopy, have demonstrated the ability of detecting biological differences between normal, precancerous and cancerous cervical pathologies using cytology samples 66 , 67 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of mass spectrometry studies have previously reported satisfactory diagnostic accuracy of cervical cancer or pre-cancer, however these were performed either on cervical tissue samples 27 , rendering it unsuitable as a screening approach, or using more laborious and time-consuming approaches 9 , [11] , [12] , [13] . Different studies employing vibrational spectroscopic approaches, including Raman and infrared spectroscopy, have demonstrated the ability of detecting biological differences between normal, precancerous and cancerous cervical pathologies using cytology samples 66 , 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The tissue-derived smoke that is created from the rapid heating contains information about the phospholipid signature of the tissue which can be used for accurate discrimination of tissue types as well as real-time, intraoperative detection of cancer or evaluation of surgical margins [24] , [25] , [26] . We have also recently shown that REIMS coupled to electrosurgery via a handheld device (also known as the intelligent knife – iKnife) permits detection of precancerous lesions and cervical cancer with high diagnostic accuracy 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In cancer research, proteome profiling is the most promising approach, but for now high-resolution mass spectrometry still lacks in many aspects, such as high costs, the required expertise (to run the instruments and analyze the data) and standardization [ 54 , 55 ]. To overcome some of these aspects, some revolutionary MS-based instruments are under development, such as the iKnife [ 56 ] and the MasSpec Pen [ 57 ], both used for intra-operatory diagnosis. The implementation of these kinds of device could also have a tremendous impact in the diagnosis of breast cancer and, therefore, a better classification and characterization of each type of cancerous tissue is mandatory.…”
Section: Perspectives Of Implementation Of Ms-based Methods For Tnmentioning
confidence: 99%
“… 44 46 It is also able to discriminate HPV infected cervical samples from those without HPV. 47 It is therefore highly likely that if present in tissue or biofluids subjected to diathermy, remnants of the SARS-CoV2 are likely to be detectable.…”
Section: Components Of Surgical Plumesmentioning
confidence: 99%